2021
DOI: 10.3390/plants11010042
|View full text |Cite
|
Sign up to set email alerts
|

Foeniculum vulgare Miller, a New Chemotype from Montenegro

Abstract: Previous studies relating to prolonged and fractionated distillation procedures highlighted essential oils’ (EOs) chemical composition to be significantly dependent on the extraction duration and harvesting time. As a continuation, a hydrodistillation procedure was applied to ripe fruit material of fennel, Foeniculum vulgare Miller (Apiaceae), collected from three localities in Montenegro (Podgorica, Nikšić, and Kotor) to furnish a total of 12 EOs. Liquid and vapor phases of the samples were analyzed by Gas Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…However, this classification is not unique. Other studies suggested the classification of even more chemotypes, for example, Mota et al (2015) [42] reported four chemotypes of F. vulgare, namely, anethole, estragole, anethole/estragole, and anethole/fenchone, while Božović et al (2021) [43] proposed the α-terpineolic chemotype as a new chemotype of fennel. Regarding the chemical composition, the literature search revealed that Mimica-Dukić et al (2003) [11] reported a total of 13 chemical constituents in an amount >0.1% in fennel seeds EO obtained under different HD conditions, where the main constituents were anethole (72.27-74.18%), fenchone (11.32-16.35%), and estragole (3.78-5.29%), which is consistent with the results of this study.…”
Section: Chemical Characterization Of Fennel Seeds Eomentioning
confidence: 99%
“…However, this classification is not unique. Other studies suggested the classification of even more chemotypes, for example, Mota et al (2015) [42] reported four chemotypes of F. vulgare, namely, anethole, estragole, anethole/estragole, and anethole/fenchone, while Božović et al (2021) [43] proposed the α-terpineolic chemotype as a new chemotype of fennel. Regarding the chemical composition, the literature search revealed that Mimica-Dukić et al (2003) [11] reported a total of 13 chemical constituents in an amount >0.1% in fennel seeds EO obtained under different HD conditions, where the main constituents were anethole (72.27-74.18%), fenchone (11.32-16.35%), and estragole (3.78-5.29%), which is consistent with the results of this study.…”
Section: Chemical Characterization Of Fennel Seeds Eomentioning
confidence: 99%
“…In previous reports, it has been demonstrated that EOs can exert either antibacterial [ 15 , 17 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] or biofilm modulation effects [ 15 , 16 , 17 , 20 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. As a continuation of a previously reported screen for antibacterial and antibiofilm EOs [ 15 , 16 , 17 , 20 , 42 ], herein, 61 previously investigated commercial samples have been evaluated for their abilities to modulate the biofilm formation of six P. aeruginosa clinical strains (22P, 25P, 26P, 27P, 37P, and 39P) in comparison with the reference strains PAO1 and PA14.…”
Section: Discussionmentioning
confidence: 99%
“…The dried aerial parts of FV, OV or TV plants were subjected to steam distillation, collecting the condensate for a period of 1 h. Steam distillation was carried out in two modalities, (1) recycled distillation (RD), from which the water/oil double phase was allowed to accumulate without interruption, and (2) continuous distillation (CD) [7][8][9][10][11][36][37][38], the conventional form of EO distillation, where the condensed water/oil layers were collected directly in a bottle during distillation. The distillation time was arbitrarily set at 1 h, which is also a more productive duration [8,9].…”
Section: Eo Steam Distillationmentioning
confidence: 99%